Yedoma Permafrost Genesis: Over 150 Years of Mystery and Controversy - Shur, Yuri; Fortier, Daniel; Jorgenson, M. Torre; Kanevskiy, Mikhail; Schirrmeister, Lutz; Strauss, Jens; Vasiliev, Alexander; Ward Jones, Melissa (Frontiers in Earth Science, 2022)
Since the discovery of frozen megafauna carcasses in Northern Siberia and Alaska in the early 1800s, the Yedoma phenomenon has attracted many Arctic explorers and scientists. Exposed along coastal and riverbank bluffs, Yedoma often reveals as large masses of ice with some inclusions of soil. The underground ice mystified numerous geologists and geographers the most, and they considered soil in Yedoma exposures as a secondary and unimportant component. Numerous scientists all over the world tried to explain the origin of Yedoma for many decades, even though some of them have never seen Yedoma in the field. The origin of massive ice in Yedoma has been attributed to buried surface ice (glaciers, snow, lake ice, icings), intrusive ice (open system pingo), and finally to ice wedges. The last hypothesis met difficulties to explain a vertical extent of ice wedges, which in some cases exceeds 40 m. It took over 150 years of intense debates to understand the process of formation of ice wedges occurring simultaneously (syngenetically) with soil deposition and permafrost aggregation. This understanding was based on observations of the contemporary formation of syngenetic permafrost with ice wedges on floodplains of Arctic rivers. Initially, it was concluded that Yedoma was a floodplain deposit and it took several decades of debates to understand that Yedoma is of polygenetic origin. In this paper, we discuss the history of Yedoma studies from the early 19th century until the 1980s – the period, when the main hypotheses of the origin of Yedoma were debated and developed.